Collaboration Between Revelation and Thought As A Method For Understanding Islamic Law - Rahmad Kartono; Kurniati Kurniati; Lomba Sultan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2023)
Religious revelation teaches two ways to acquire knowledge. First, through revelation, namely through communication from God to humans, and secondly through reason or thought, namely using impressions obtained by the five senses as food for thought to arrive at conclusions. Knowledge obtained through revelation is believed to be absolute knowledge, while knowledge obtained through reason is believed to be relative knowledge, which requires continuous testing, can be right and can be wrong. In contrast to the revealed religion, the earthly religion departs from the knowledge acquired. through contemplation, to gain truth and enlightenment. In the age of scientific and technological advances, the question arises, which knowledge is more trusted, knowledge obtained through thought, knowledge through revelation, or knowledge obtained through both.